Tinjauan Hukum Islam Terhadap Sebab Dan Halangan Waris-Mewaris - Siti Maryam Qurotul Aini (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
The problem of dividing inheritance from the past, now and even in the future is a common thing. Lack of knowledge of Islamic law governing inheritance is one of the reasons this phenomenon occurs. This paper is here to explain how the causes and barriers to inheritance inherit the perspective of Islamic law. This study concludes that the distribution of inheritance to the heirs is in accordance with the provisions of the Qur'an, As-Sunnah, and the agreement of the Ulama (ijma'). This begins by giving inheritance to ashhabul furudh (heirs whose share has been determined). There are three reasons for inheritance, namely: true kinship (those with nasab ties), marriage, al-wala. Meanwhile, there are three reasons for not getting an inheritance, namely: a servant or slave, because of killing, and differences in religion. Mahrum is a term for someone who belongs to one of the three causes that can invalidate his inheritance rights. While mahjub is the loss of one's inheritance rights because there is an heir who is closer to the heir.